INNOVATION OF ECONOMIC SUSTAINABILITY AND ITS MEASUREMENT IN HOTEL INDUSTRY - Tučková, Zuzana; Vaculčíková, Zuzana (Department of Economics, Faculty of Arts, University of Colombo, 2018)
High competitiveness in tourism businesses puts a pressure on solving and improving financial results. One way how to reach economically stable tourism business is to concentrate on sustainability and its integration into planning and policy. By integrating sustainable elements, tourism businesses may be considered innovative and more competitive in the eyes of their clients and it can be helpful for the management, too. Thus, tourism management should solve innovation, competitiveness and sustainability in order to benefit tourism economy. The aim of this paper is to determine the relevance of the economic sustainability in the hotel industry in chosen region in the Czech Republic and to clarify indicators to monitor economic sustainability in the field of hotel facilities as a possible innovative element of economic side of hotels. Methodologically, Delphi study is used to gather opinions on economic sustainability and its measurement in the chosen hotels in the Czech Republic.
Keywords: competitiveness, economic sustainability, innovation, hotel, measurement